2019
DOI: 10.1111/jphd.12317
|View full text |Cite
|
Sign up to set email alerts
|

Broken smiles: The impact of untreated dental caries and missing anterior teeth on employment

Abstract: Objectives We aimed to quantify the impact of dental caries and missing anterior teeth on employment, estimate the impact of a routine dental visit on the health of anterior teeth, and the benefits of expanding dental coverage for nonelderly adults. Methods We used the 2013–2014 Continuous National Health and Nutritional Examination Survey to develop a dental problem index (DPI) using tooth counts and tooth surface conditions. We estimated the impact of DPI on employment with logistic regression, controlling f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 20 publications
4
13
0
1
Order By: Relevance
“…Studies have suggested that poor dentition is, indeed, a predictor of low SES, e.g. because individuals with "poor oral health" are less likely to be selected at job interviews [35,36]. However this type of reverse causation is less likely for education, since missing teeth is less likely to affect educational attainment.…”
Section: Plos Onementioning
confidence: 99%
“…Studies have suggested that poor dentition is, indeed, a predictor of low SES, e.g. because individuals with "poor oral health" are less likely to be selected at job interviews [35,36]. However this type of reverse causation is less likely for education, since missing teeth is less likely to affect educational attainment.…”
Section: Plos Onementioning
confidence: 99%
“…Prevalence of tooth loss increases gradually with age [1] and in adolescents is associated with a number of deleterious outcomes including poor self-esteem [2], low quality of life [3], impact on daily performance [4], as well as impacts on social relations, and labor market outcomes (employability) [5]. It is worth noting that tooth loss before age 35 may be a risk factor for Alzheimer's disease at 65 years or over [6].…”
Section: Introductionmentioning
confidence: 99%
“…COVID‐19 has exacerbated persistent socioeconomic disparities in health outcomes and social risk factors at a time when health agencies are anticipating less revenue and increasing Medicaid enrollees. The ramifications of undervaluing oral health undermine overall health, economics, gainful employment, mental health, school and work performance, and socialization 8–10 . In order to reinforce the value of oral health care and its integral influence on overall health, we propose three domains of oral health investments and care advancements for financial viability and improved population health.…”
Section: Figurementioning
confidence: 99%
“…The ramifications of undervaluing oral health undermine overall health, economics, gainful employment, mental health, school and work performance, and socialization. [8][9][10] In order to reinforce the value of oral health care and its integral influence on overall health, we propose three domains of oral health investments and care advancements for financial viability and improved population health. The interventions within this domain framework can advance patient and provider well-being while reducing the cost burdens associated with poor quality of life due to oral disease.…”
mentioning
confidence: 99%